Concurrent Trigeminal Neuralgia and Hemifacial Spasm due to Anterior Inferior Cerebellar Artery Tortuosity: A Rare Case Report - Ankita Thakur; Paresh Korde; Abhiram Sai; Prachi Wankhade (Journal of Clinical and Diagnostic Research)
The Anterior Inferior Cerebellar Artery (AICA) plays an important role in the pathophysiology of both Hemifacial Spasm (HFS) and Trigeminal Neuralgia (TN). The AICA follows a tortuous course, which may affect the facial nerve and trigeminal nerve by compressing these structures. This compression is the common underlying aetiology for both TN and HFS. To date, TN remains an idiopathic condition that is hypothesised to be caused by an underlying irritative lesion involving the trigeminal ganglion. TN is characterised by paroxysmal, lancinating, unilateral pain, often localised along the maxillary (V2) and mandibular (V3) divisions of the trigeminal nerve. In contrast, HFS manifests as involuntary, irregular, or tonic contractions of the facial muscles. It typically begins in the orbicularis oculi and progressively spreads to involve the perioral, platysmal and lower facial muscles. Unlike TN, HFS persists even during sleep and worsens over time. The present case report discusses a 65-year-old male who presented a rare combination of TN characterised by continuous pain and HFS; the concomitant occurrence of both conditions is unique in itself. The present case demonstrates how a dilated, tortuous AICA loop causes a particularly peculiar presentation in a patient, involving both TN and HFS, along with the surgical management and treatment that facilitated a good prognosis for the diagnosis. Additionally, it highlights the rarity of these manifestations stemming from a single aetiological agent, specifically a dilated Anterior Inferior Cerebellar Artery (AICA) loop. Furthermore, it underscores the importance of early diagnosis, neuroimaging and timely surgical intervention, particularly when addressing uncommon neurovascular conflicts that manifest with overlapping cranial neuropathies.